Secret of the spiritkeeper - Forbeck, Matt.; Fiegenshuh, Emily (Renton, WA : Mirror Stone ; [New York] : Distributed in the U.S. by Holtzbrinck, 2004)
The Knights of the Silver Dragon go the the Dungeons of Doom where they must outwit zombies and goblins in order to find the secret that can save their friend Zendric the wizard.
008-up.
8 13
Keywords: Knights and knighthood -- Fiction; Wizards -- Fiction; Secrecy -- Fiction; Fantasy fiction